Hybrid Repair of Kommerell Diverticulum and Aberrant Subclavian Artery with Compressive Symptoms and a New Strategy: Case Report - Tsukagoshi, Junji (Ann Vasc Dis, 2021)
Surgical indication and treatment for patients with Kommerell diverticulum and aberrant subclavian artery are still not well established. A patient with esophageal and tracheal compression resulting from these anatomical abnormalities was successfully treated with a hybrid approach of total arch replacement, frozen elephant trunk technique, aberrant left subclavian artery transection, and left subclavian artery reconstruction through median sternotomy. Compressive symptoms were relieved without resecting the enlarged diverticulum. In this case, the importance of preoperative investigation for the main cause of compressive symptoms is illustrated and a novel treatment strategy is outlined.